2014
DOI: 10.1016/j.egypro.2014.11.946
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Design of an Active Façade System with Peltier Cells

Abstract: The research is looking for an innovative self-sufficient, industrialized and lightweight façade module that integrates a thermoelectric HVAC system. The principal aim of the research was to try providing a built answer to the current efficiency objectives (Directive 2010/31/CE), creating a façade solution that can be installed in new buildings or in already existing ones. This report tries to explain the theoretical design of this new façade system with Peltier cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…This work contributes in identifying the key aspect that may increase the efficiency of the HVAC systems in ventilated façades. Also, this research completes the authors' previous work [33][34][35][36][37] about the theoretical design and construction of an active ventilated façade with Peltier modules. The authors are aware that a techno-economic analysis of a THU prototype has not yet been reported.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This work contributes in identifying the key aspect that may increase the efficiency of the HVAC systems in ventilated façades. Also, this research completes the authors' previous work [33][34][35][36][37] about the theoretical design and construction of an active ventilated façade with Peltier modules. The authors are aware that a techno-economic analysis of a THU prototype has not yet been reported.…”
Section: Introductionsupporting
confidence: 82%
“…The result was the construction of a simplified inhabited housing unit (prefabricated module) with a thermoelectric heating system. A detailed report on this first THU version (v1.1) and its manufacture has been presented by the authors in previous works [33][34][35][36]. This section provides a brief description of this first version and presents the improvement of this prototype (THU v1.2).…”
Section: Technical Description Of the Thermoelectric Heating Unitsmentioning
confidence: 99%
“…It is clearly visible in the studies that most of them do not provide experimental testing and develop prototypes for a pilot building. It is sometimes the case that a specific mix of technologies is investigated in a theoretical design but not accompanied with detailed energy modeling or experimental investigations [80]. This seems to be a key specific issue that needs to be attended to in future research by focusing on more combination of simulation and experimental work that involves field-testing.…”
Section: Discussion and Roadmapmentioning
confidence: 99%
“…For example, mechanical ventilation with heat recovery in air-based ADBEs has been studied in [78,79] to reduce energy losses of the envelope. Furthermore, either with or without mechanical ventilation, it is proposed to close the air cavity during certain occasions in order to avoid negative effects on occupants' thermal comfort caused by undesired ambient conditions [80]. Additionally, given the fact that the pre-heating of the air flowing in the cavity increases the efficiency of the air-based ADBE, geothermal energy systems are proposed to be integrated into the overall system [81,82].…”
Section: Air-based Adbementioning
confidence: 99%
“…La idea de esta iniciativa nace del trabajo de un equipo de investigación centrado en el acondicionamiento higrotérmico con termoelectricidad, utilizando células Peltier como medio para la transferencia de calor (Ibáñez-Puy et al, 2014;Ibañez-puy et al, 2017;María Ibañez-Puy et al, 2018;Ibañez-Puy et, 2015;Martín-Gómez et al, 2010). El estudio de esta tecnología, así como su evidente interés docente, han dado como resultado el desarrollo de una sesión práctica que acercan la investigación y la termoelectricidad a los futuros profesionales, al mismo tiempo que les permite interiorizar conceptos básicos para su formación.…”
Section: Desarrollo De La Innovaciónunclassified